A patient journey analysis: Identification and treatment of dementia with Lewy bodies: Developing topics. (7th December 2020) - Abler, Victor; Rashid, Nazia; Skoog, Ben; Halpern, Rachel; Bunner, Scott; Frazer, Monica S.
Abstract: Background: Between 3.2%‐7.1% of dementia patients are diagnosed with DLB. There is limited research on the identification and treatment of DLB, indicating an unmet need for this condition.[2] [1] Hogan D, Fiest K, Roberts J, Maxwell C, Dykeman J, Pringsheim T, Jetté N. (2016). The Prevalence and Incidence of Dementia with Lewy Bodies: A Systematic Review. Canadian Journal of Neurological Sciences / Journal Canadien Des Sciences Neurologiques, 43 (S1), S83‐S95. doi:10.1017/cjn.2016.2. [2] Monfared A, Meier G, Perry R, Joe D. Burden of disease and current management of Dementia with Lewy Bodies: a literature review. Neurol Ther, 2019, 8:289‐305. Method: This claims‐data analysis examined commercial and Medicare Advantage with Part D (MAPD) enrollees aged ≥40 years with ≥2 DLB diagnoses from 01Jun2016–31May2018. The earliest DLB diagnosis was the index date. Continuous insurance enrollment was required from 24 months before to 12 months after index. Patient characteristics, diagnoses, medication utilization, symptoms (e.g. behavioral, movement changes), and imaging tests were measured in 6‐month periods pre‐ and post‐index. Result: The 974 patients identified had mean age of 78.3 years, were 56.6% male, 90.0% were MAPD enrollees, and had a mean Charlson comorbidity score of 2.87 (SD=2.05). Generally, percentages of patients with ≥1 diagnosis in a dementia or symptom change category or with ≥1 pharmacy fill for an antipsychotic or behavioral health (BH) medication (e.g., antidepressants, anxiolytics) trended higher in each 6‐month period prior to index date, were highest in the 6 months beginning on index, and decreased slightly 7‐12 months post‐index. Across periods, 31%‐90% of patients had multiple types of dementia diagnoses. BH medications (52.4%‐63.9% with ≥1 BH medication fill across periods) were prescribed to DLB patients more often than were antipsychotics (14.2%‐31.5% with ≥1 antipsychotic fill). CT scans (10.6%‐27.5%) and MRIs (5.3%‐13.0%) were the most prevalent imaging tests. Conclusion: Percentages of patients with imaging tests, DLB symptoms, diagnoses and treatments for DLB increased as patients' first DLB diagnosis neared and occurred at lower percentages 7‐12 months after initial diagnosis.